2017
DOI: 10.1002/jhet.2875
|View full text |Cite
|
Sign up to set email alerts
|

Double Hydroamination of Alkyne via PTC and Microwave‐activated Diastereoselective Synthesis of 2,3‐dihydroimidazo[1,2‐a]pyridine in an Aqueous Media

Abstract: A novel facile and diastereoselective synthesis of imidazopyridine with high atom economy in water as a green solvent under synergic effect of microwave activation and phase transfer catalysis from readily available 2‐aminopyridine and electrophilic alkyne, dimethyl acetylene dicarboxylate has been developed. The strategy of the protocol involves heterocyclisation via double hydroamination of dimethyl acetylene dicarboxylate in biphasic system catalyzed by benzyltriethylammonium bromide activated by microwave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In 2017, by extending his previous work and using PTC (phase transfer catalysis), Waseem et al [190] . reported a versatile, cost‐effective and diastereoselective synthesis of 2,3‐dihydro imidazo[1,2‐ a ]pyridine 251 from 2‐aminopyridine derivatives 249 and electrophilic alkyne 250 in water as a green solvent.…”
Section: Development Of Various Methods Towards the Synthesis Of Imid...mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, by extending his previous work and using PTC (phase transfer catalysis), Waseem et al [190] . reported a versatile, cost‐effective and diastereoselective synthesis of 2,3‐dihydro imidazo[1,2‐ a ]pyridine 251 from 2‐aminopyridine derivatives 249 and electrophilic alkyne 250 in water as a green solvent.…”
Section: Development Of Various Methods Towards the Synthesis Of Imid...mentioning
confidence: 99%
“…In 2017, by extending his previous work and using PTC (phase transfer catalysis), Waseem et al [190] reported a versatile, cost-effective and diastereoselective synthesis of 2,3-dihydro imidazo[1,2-a]pyridine 251 from 2-aminopyridine derivatives 249 and electrophilic alkyne 250 in water as a green solvent. They developed it under the synergic effect of microwave activation and phase transfer catalysis by double hydroamination of 2-aminopyridine on DMAD (dimethyl acetylenedicarboxylate) via aza-Michael addition resulting in intramolecular heterocyclization in good yields with high trans-diastereoselec-tivity.…”
Section: Microwave-assisted Reactionsmentioning
confidence: 99%
“…Recently, several protocols have already been described the synthesis of thiazoles and benzothiazoles derivatives [6][7][8]. The new trend for the synthetic of compounds uses microwave irradiation (MWI) as a powerful technique for rapid and efficient synthesis [15][16][17]. Several pyrimidine derivatives exhibit diverse pharmacological activities [9,10], as antimicrobial [11], analgesic [12], anti-inflammatory [13], and antitumor activity [14].…”
Section: Introductionmentioning
confidence: 99%
“…Ethyl ethoxyacetate was not isolated, perhaps because the competing hydrolytic or oxidative decomposition of the carbene complex I could also occur in the medium. Alternative mechanisms can, of course, be envisaged, in particular through the initial [3 + 2] peri -condensation of aminopyridine with the alkyne substrate, as very recently proposed to occur under microwave activation conditions . The putative [3 + 2] cycloadduct K has the same molar mass as the Michael adduct 4 , above-assigned to the corresponding HRMS peak.…”
mentioning
confidence: 99%
“…Alternative mechanisms can, of course, be envisaged, in particular through the initial [3 + 2] peri-condensation of aminopyridine with the alkyne substrate, as very recently proposed to occur under microwave activation conditions. 14 The putative [3 + 2] cycloadduct K has the same molar mass as the Michael adduct 4, above-assigned to the corresponding HRMS peak. However, disruption of the aromatic character of the original pyridine ring is anticipated to significantly destabilize K with respect to 4.…”
mentioning
confidence: 99%